2018
DOI: 10.1371/journal.pone.0205404
|View full text |Cite
|
Sign up to set email alerts
|

Nest sites as a key resource for population persistence: A case study modelling nest occupancy under forestry practices

Abstract: Natural nest sites are important breeding resource in terms of population dynamics, especially in forest systems where nest trees limit populations or timber harvesting destroys nests. Nest structures usually have a long life and can be reused by breeding pairs across multiple breeding seasons, so studying their dynamics is of relevance for biodiversity conservation. In this study, we develop a dynamic model to evaluate nest site availability and its influence on the breeding settlement of a forest raptor comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
3
0
2
Order By: Relevance
“…Previous studies found harvest activities at the nest-stand scale resulted in fewer nests used by goshawks (Byholm et al 2020), and goshawk nest sites or territories with less harvest nearby or with relatively large trees were more likely to be occupied (Rodriguez et al 2016). Harvest limits available nest sites and use by forest-dwelling raptors (Jiménez-Franco et al 2018). Therefore, retaining natural stand structure and limiting extensive commercial treatments is important, but pre-commercial thinning could be used to improve structure in nest areas of forest-dwelling raptors (Lõhmus 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found harvest activities at the nest-stand scale resulted in fewer nests used by goshawks (Byholm et al 2020), and goshawk nest sites or territories with less harvest nearby or with relatively large trees were more likely to be occupied (Rodriguez et al 2016). Harvest limits available nest sites and use by forest-dwelling raptors (Jiménez-Franco et al 2018). Therefore, retaining natural stand structure and limiting extensive commercial treatments is important, but pre-commercial thinning could be used to improve structure in nest areas of forest-dwelling raptors (Lõhmus 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A més, el 100% dels nius localitzats al final d'aquesta darrera campanya (n=46) es troben a les zones definides amb el 60% d'idoneïtat. El model, per tant, sembla una eina útil per obtenir una cartografia predictiva de la presència d'astor, primer objectiu del treball, i delimitar aquelles zones de bosc millor conservades a escala arbre, tal i com definien a priori els treballs de Sergio et al (2005), García-Salgado (2018) i Jiménez-Franco et al (2018. També es va poder observar a la representació del model que, a aquesta escala, les zones potencialment favorables es trobaven dins de rodals més o menys extensos de pi blanc.…”
Section: Territory-scale Graphs (500 M) A) Proportion Of Aleppo Pine ...unclassified
“…Els models a escala de territori i, especialment, el de rodal, aporten localitzacions d'hàbitat òptim continu dins els forests que poden abastar fins a desenes d'hectàrees. Aquesta extensió correspon aproximadament amb les àrees immediatament al voltant dels nius utilitzats, però també conté, si hi són presents, altres nius coneguts d'altres anys que s'han rebutjat, essent la preservació del conjunt de tots els nius de gran importància per a la conservació dels rapinyaires forestals (Jiménez-Franco et al 2018). Els indrets amb major desenvolupament dels arbres són els primers rodals que es tallen, ja siguin per treballs silvícoles de prevenció d'incendis o aprofitaments forestals.…”
Section: Territory-scale Graphs (500 M) A) Proportion Of Aleppo Pine ...unclassified
“…These effects can escalate to affect the structure and dynamics of animal communities. Examples of limiting resources affecting bird and mammal communities include shared prey (Gilg et al., 2003 ), nectar‐producing flowers (Guevara et al., 2023 ), and cavities for nesting birds (Jiménez‐Franco et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%